ANALISIS EKONOMI USAHA PEMBIBITAN CABAI (Capsicum annuum L.) DENGAN TIGA JENIS BENIH DAN PERLAKUAN PEMUPUKAN - JUJUK JUHARIAH; MARGARETHA PRABA AULIA (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
The purpose of this study was to determine the most effective treatment of fertilizing doses on the results of quality tests of sprouts and growth of chilli seeds (Capsicum annuum) between bulk seeds, seeds in packaging, and direct extraction results seeds. The experimental method used was a factorial randomized block design. The first factor is the type of seeds, namely: bulk seeds (A), in packages (B), and direct extraction results (C). The second factor is the fertilizer dosage using NPK